Facility maintenance in ‘Program Perumahan Rakyat’ low-cost housing scheme in Malaysia: issues and challenges - Daud, Mahyuddin; Mat Isa, Norlaili; Mohd Roslan, Norul Syakila (LexisNexis Malaysia Sdn Bad, 2018)
Effective facility maintenance of high-rise properties has become alarming issues for decades. Even though most high-rise residences in Malaysia fall under the purview of the Housing Development (Control and Licensing) Act 1966 and the Strata Management Act 2013, the 'Program Perumahan Rakyat' ('PPR') Low-Cost Housing Scheme is a peculiar exception. Firstly introduced by the federal government to curb squatting issues in urban areas, the PPR Housing Scheme was not subjected to any legislations nor written agreements between residents and government. This had triggered the issue on ineffective facility management after project completion. Due to the absence of appropriate legislations or guidelines, the big question was:who should maintain the PPR? -- or rather, from whose pocket should the funding come from? With low rental collection and limited financial resources, facilities were left unmaintained and badly damaged prior to a residents' occupation. PPR residents risk their lives living in an inhabitable environment due to poor facility maintenance. Secondly, there exists jurisdictional conflicts between federal and state governments on the issue of federal level involvement to legislate on behalf of the state as allowed by art 76 of the Federal Constitution. Federal government involvement may occur to ensure uniformity between federal and state laws. PPR Housing Scheme is one example of such, where the scheme was created by the federal government and assigned to the state for management. This however, was made in the absence of clear legislations or guidelines, leaving the state clueless on how to implement federal legislations at their level. This article suggests that federal and state governments must collaborate and allocate adequate resources for effective facility maintenance of PPR Homes. Further, appropriate PPR mechanisms should be in place to ensure adequate and regular maintenance without affecting PPR residents' quality of life. This guarantees every citizen of Malaysia can afford to own homes without compromising their quality of life.